Relayout planning to reduce waste in food industry through simulation approach - Muhammad, Faishal (2015)
Layout planning is one of the most important factors that must be considered if a company wants to become more competitive particularly in the cost, delivery and quality. A good layout can streamline transportation directly influence the cost and delivery time. This research is based on case in a food company in Indonesia. This company produces snack. The characteristic of this production process is make to stock system with 24-working hours. From the observation of the production process, it indicates that layout planning is ineffective. This showed on long distance moved of items, high number of worker and low throughput as well. The aim of this research is to re-layout in order to improve throughput and also reduce number of workers and the distance. A conceptual model was developed to determine the experimental factors and responses of the system. To solve this problem, three alternative layout were developed by using MULTIPLE method. These alternative layouts were then translated and analyzed into operational models using the ProModel 6.0 Simulation Software. The results indicates an improvement of throughput by 15% for alternative 1, 28% for alternative 2, and 21% for alternative 3. And for the number of worker indicates an improvement by reduce worker 13% for alternative 1, 2, and 3. For the distance indicates an improvement by reduce distance 83% for alternative 1, 87% for alternative 2, 86% for alternative 3. Generally, alternative 2 give the largest improvement than other although need more expensive cost investment.